Komunikasi Interpersonal dalam Pelayanan Publik (Telaah Teoritis pada Pelayanan Pendaftaran Calon Jamaah Haji di Kota Bengkulu) - Dwi Aji Raharjo (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2015)
As a public servis departement, the Ministry of Religions affair had become public attention. Moreover, in haj applicant registration services. Recently, more people want to accomplish haj. The effective interpersonal communication should be mastered by the haj officials. Since the communications is the base in a organization. Best services can give positive impact to the ministry, as the public services executor